A shake table test study of reinforced concrete shear wall model structures exhibiting strong non-linear behaviors. (1st June 2020) - He, Jingran; Chen, Jianbing; Ren, Xiaodan; Li, Jie
Highlights: Shake table test of two concrete shear wall structural models are presented. Complete compressive constitutive law of concrete prisms are tested. Strong nonlinear behavior without damage accumulation is guaranteed by design. The flexural-shear damage and compressive damage occurred in the shake table tests. Elaborate analyses of the tests include frequencies, displacement, …, among others. Abstract: Shake table test is one of the most important manners for the performance evaluation of structures under strong earthquakes and for the verification of refined numerical simulation methods. To this end, in the present paper, shake table tests on two concrete shear wall model structures, together with the tests of complete uniaxial compressive constitutive curves of concrete, were carried out. The purpose of the tests is to provide quantitative benchmark results for the verification and improvement of refined multi-scale numerical simulation method for structures exhibiting strong non-linear behaviors. Three important properties were carefully taken into account in the tests, including: (1) The scale ratio should not be too small so that detailed local damage could be revealed and the experimental results could serve as benchmark data; (2) The model structures should exhibit strong nonlinear behaviors but the accumulated damage between load cases should be avoided; (3) Concrete specimens should be simultaneously tested to capture the complete stress-strain curves rather than only the two parameters (the compressive strength and Young's modulus); and (4) The unavoidable randomness involved in concrete structures should be quantified. To satisfy the above requirements, some special measures were taken, including: e.g., vertical prestressed tendons were exerted to make up the inadequacy of gravitational compression due to the inadequate density scaling; strong earthquake inputs were input directly after linear stage tests so that strong non-linearity occurred directly in the model structures, similar to practical structures subjected to real earthquakes; and 54 concrete specimens were tested for constitutive law and two model structures were tested for comparison and characterizing the effects of randomness. The experimental results, including frequencies and vibrational modes, the observed damage distributions and the responses of model structures are elaborately delineated and discussed in the paper. In particular, besides flexural-shear damage, compressive damage was also observed in the test model structures. This is frequently observed in practical earthquake damage but is usually not exhibited in most shake table tests. Such detailed information together with observed data provided valuable benchmark data for the verification and improvement of refined numerical simulation method, which will be detailed in other papers.